Negative Predictive Value of Endobronchial Ultrasound–guided Transbronchial Needle Aspiration. Issue 2 (March 2016) - Bellinger, Christina R.; Ruiz, Jimmy; Dotson, Travis
Abstract : Endobronchial ultrasound (EBUS)-guided transbronchial needle aspiration is now the standard care for minimally invasive staging of the mediastinum. A literature review of EBUS was performed in its use for diagnosing and staging lung cancer and for staging extrathoracic malignancies. We evaluated the negative predictive value of EBUS in varying diagnostic scenarios.